Untangling the influence of ecological and evolutionary factors on trait variation across hummingbird assemblages (2012)
ABSTRACT: Phylogenetic community ecology combines phylogenetic hypotheses with localspecies composition and functional-trait information to evaluate historical and contemporarymechanisms inﬂuencing local assemblage structure. Most studies assume that, if functionaltraits are conserved, then patterns of trait variation should match patterns of phylogeneticstructure within local assemblages. Here we evaluated if we could predict trait structure byassuming that environmental ﬁltering or biotic interactions work primarily on phylogenet-ically conserved functional traits. We investigated patterns of phylogenetic assemblagestructure and functional-trait variation in bill length, wing length, and body mass in 236hummingbird assemblages (126 species) across two major gradients in northern SouthAmerica: elevation and precipitation. While mean trait values for assemblages varypredictably based on empirical knowledge of hummingbird biology, the distribution of traitvalues within assemblages do not correspond to those predicted based on phylogenetic signaland phylogenetic structure. Instead, we were able to identify instances where assemblages havehigh levels of morphological variation despite their close evolutionary relatedness and viceversa. Our results provide support for both ﬁltering and biotic interactions across gradients, ashas been documented in other studies